ANALISIS KEBIJAKAN EKONOMI: RESTRUKTURISASI UTANG SELAMA PANDEMI COVID-19 - Riki Firmansah; Syamsir; Aldri Frinaldi; Anjas Muharman (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The Covid-19 pandemic has had a significant impact on the economy. This also causes many customers to have difficulty paying their debts. This study aims to look at the economic policies carried out by the government to be able to carry out debt restructuring during this pandemic. This research was then carried out using an empirical juridical approach. The results of this study then show that many Micro, Small and Medium Enterprises (MSMEs) entrepreneurs experience difficulties in paying their debt obligations. This is because their business has been greatly affected by the existence of the pandemic, either directly or indirectly. The current debt restructuring is going quite well. This policy also then makes credit quality smooth and no longer jammed.